2010
DOI: 10.3354/meps08507
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem engineering by burrowing crabs increases cordgrass mortality caused by stem-boring insects

Abstract: Some studies have shown that the balance between top-down and bottom-up processes is context dependent, but few have tested how biotic interactions can affect this balance. We quantified the attack frequencies by the stem borer moth Haimbachia sp. nov. on the cordgrasses Spartina densiflora and S. alterniflora in 5 marshes of the southwestern Atlantic coastline, located between 36°S and 41°S. We examined whether ecosystem engineering by burrowing crabs Neohelice (Chasmagnathus) granulata, which improves plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Indeed, the positive effect of crab burrowing on plant production is then translated to higher trophic levels, benefiting rodents (Akodon azarae and Oligoryzomys flavescens: Canepuccia et al, 2008) and stem-borer moths (Haimbachia sp. : Canepuccia et al, 2010a). Similarly, bioturbation by a small crustacean (Orchestia gammarellus) on northern European Atlantic marshes has recently been hypothesized to be important for the establishment of anoxia-intolerant plant species such as Elytrigia atherica (Schrama et al, 2012).…”
Section: Elevation (And Its Effects On Oxygen Availability and Salinity)mentioning
confidence: 99%
“…Indeed, the positive effect of crab burrowing on plant production is then translated to higher trophic levels, benefiting rodents (Akodon azarae and Oligoryzomys flavescens: Canepuccia et al, 2008) and stem-borer moths (Haimbachia sp. : Canepuccia et al, 2010a). Similarly, bioturbation by a small crustacean (Orchestia gammarellus) on northern European Atlantic marshes has recently been hypothesized to be important for the establishment of anoxia-intolerant plant species such as Elytrigia atherica (Schrama et al, 2012).…”
Section: Elevation (And Its Effects On Oxygen Availability and Salinity)mentioning
confidence: 99%
“…As an interface, tidal marshes share characteristics with their neighboring habitats but have their own unique features (Mitsch & Gosselink 1993), such as having strong physical gradients (Bertness 1991, Bertness et al 1992 and being dominated by a few very widespread species which develop under a wide range of environmental harshness conditions across large geographic regions (Mitsch & Gosselink 1993, Pennings & Bertness 2001, Isacch et al 2006). Recently, large-scale studies have found that herbivore−marsh plant interactions are more intense at lower latitudes along the east coast of North America (Salgado & Pennings 2005, Pennings et al 2009), in Europe (Pennings et al 2007) and in South America (Canepuccia et al 2010a(Canepuccia et al , 2011 and that variation in grazing intensity may be related to changes in herbivore densities among locations (Alberti et al 2007, Pennings et al 2009). However, information is scarce about the environmental variables that shape the geographical zoning and distribution of vegetation in tidal marshes.…”
Section: Introductionmentioning
confidence: 97%
“…Haimbachia sp. nov. is a common herbivore in SW Atlantic marshes (Canepuccia et al 2010a). As a result of the damage caused by the feeding of the moth larvae, Spartina spp.…”
Section: Discussionmentioning
confidence: 99%
“…nov. is an herbivore specific to the Spartina plant. The abundance of this species decreases towards higher latitudes (Canepuccia et al 2010a). Larvae overwinter inside Spartina stems, with only one larva per stem (A. D. C. pers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation